2018
DOI: 10.1093/carcin/bgy158
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin A gains in antiproliferative capacity by reducing the glycolytic potential via the p53/TIGAR axis in colon cancer cells

Abstract: Urolithin A inhibits growth of colon cancer cells alone and synergistically in combination with oxaliplatin. Those activities are markedly supported by activation of the p53/TIGAR axis and subsequent reduction of the cellular glycolytic potential by urolithin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 51 publications
4
29
1
Order By: Relevance
“…More recent evidence[ 28 ] showing a dose-dependent anti-clonogenic effect of long-term exposure to UA in CRC cell lines, indicates that a decrease in the colony formation is exerted through the senescence induction via the p53/p21 pathway, rather than by cell cycle arrest or apoptosis, which required much higher concentrations[ 28 ]. These data are consistent with previous results[ 32 ], also suggesting that the antiproliferative effect of long-term exposure to UA in a colon cancer cell line was mediated through the p53/p21-dependent senescence-like growth arrest. This action was synergistic with the standard chemotherapeutic drug oxaliplatin[ 32 ].…”
Section: Intestinesupporting
confidence: 93%
See 1 more Smart Citation
“…More recent evidence[ 28 ] showing a dose-dependent anti-clonogenic effect of long-term exposure to UA in CRC cell lines, indicates that a decrease in the colony formation is exerted through the senescence induction via the p53/p21 pathway, rather than by cell cycle arrest or apoptosis, which required much higher concentrations[ 28 ]. These data are consistent with previous results[ 32 ], also suggesting that the antiproliferative effect of long-term exposure to UA in a colon cancer cell line was mediated through the p53/p21-dependent senescence-like growth arrest. This action was synergistic with the standard chemotherapeutic drug oxaliplatin[ 32 ].…”
Section: Intestinesupporting
confidence: 93%
“…These data are consistent with previous results[ 32 ], also suggesting that the antiproliferative effect of long-term exposure to UA in a colon cancer cell line was mediated through the p53/p21-dependent senescence-like growth arrest. This action was synergistic with the standard chemotherapeutic drug oxaliplatin[ 32 ]. González-Sarrías et al[ 33 ] have also demonstrated that UA at concentrations achievable in the human colorectum, can potentiate the anticancer effects of 5-fluorouracil (5-FU) on human colon cancer cells.…”
Section: Intestinesupporting
confidence: 93%
“…Norden and Heiss also reported that urolithin A-induced p53 stabilization in HCT-116 cells not only exerted antiproliferative effects (IC 50 = 19 μ M) but also synergized with the anticancer drug oxaliplatin. In the absence of p53, a significant decrease in urolithin A antiproliferative activity was however noted (IC 50 = 38 μ M) [ 80 ].…”
Section: Urolithin Activity In the Modulation Of Oxidative Stressmentioning
confidence: 99%
“…Nevertheless, EA is poorly absorbed and quickly eliminated, and the biological activity of EA is controversial. Interestingly, recent published studies have described the biological effects of UA, including anti-proliferation in cancer, antiinflammation, anti-oxidant activity, improved lipid metabolism [13][14][15]. UA inhibits the catabolic effect of TNF-α on nucleus pulposus cells and alleviates intervertebral disc degeneration in vivo [16].…”
Section: Introductionmentioning
confidence: 99%